OFR-97-78 Design, Fabrication And Field Testing Of Remotely Operated Longwall Head/Tail Supports - Alfred Bellows (The National Institute for Occupational Safety and Health (NIOSH), 1978)
The objective of this contract is to design, build and demonstrate a support system to improve roof control in the entries of longwall mines. The objective of this phase has been the detailed design of such a system and the selection of a test site in which to perform the pilot demonstration. The result is a complete set of detail drawings or specifications which define the three major components of the system. The Gate Support is a variation of a face chock which has an extended canopy and additional hydraulic legs to protect the region of the face-entry intersection. The Entry Support is a steel beam and hydraulic prop set which is reusable and serves to support the first 100 or more feet of entry inby the longwall face. The Transporter is a bolter-like vehicle with a crane used for installing and retreating the beam sets. The test site selected is CF&I's Allen Mine in Colorado. They presently use simi¬lar steel beams and expect the FMA support system to be more effective as well as recoverable. It is recommended that the completed drawings be used to build a prototype system and test it first in a remote section of the mine and then in the active longwall tail entry.